Carbon quantum dots: An environmentally friendly and valued approach to sludge disposal - Rossi, Bruno L.; Andrade, Cláudia M. B.; Therézio, Eralci M.; Ramos, Romildo J.; Vasconcelos, Leonardo G.; Terezo, Ailton J.; De Siqueira, Adriano B. (Frontiers in Chemistry, 2022)
Sewage sludge, produced daily and inherent to urban development, presents problems of disposal that are still challenging today. Its disposal still offers palliative solutions, where the final destination is generally in landfills or, restrictively, to use in agriculture. The synthesis of carbon quantum dots (CQDs) from sewage sludge is a better alternative to use the stock of organic material present in the sludge. The current work sought a new alternative for the final disposal of sewage sludge, using green chemistry principles, and in order to take advantage of its intrinsic carbon stock, using it as a raw material in the production of CQDs. The obtained have a core structure mainly composed of sp2 carbon and nitrogen. The surface functional groups containing sulfur, nitrogen, and oxygen of CQDs were investigated using FTIR and TG/DSC coupled FTIR techniques. The CQDs showed a luminescence decay time equivalent to fluorescent compounds and with satisfying quantum yield since no passive/oxidizing agent or material purification process was used. The photoluminescence spectroscopy analysis showed that the CDQs excitation λmax was at 360 nm and caused a λmax emission at 437 nm (CQDsa) and 430 nm (CQDsb). The CQDs obtained showed sizes of 9,69 ± 2,64 nm(CQDsa) and 10,92± 2,69 nm (CQDsb). In vitro experiments demonstrated the uptake of CQDs by the endothelial cell line EAhy 926 and their non-toxicity.